Efficient α-Arylation of α-Fluoro-α-nitrosulfonylmethanes Employing Diaryliodonium Salts - Zaheer, Mohd Khalid; Vaishanv, Narendra Kumar; Kumar, Awadhesh; Mishra, Sameer; Kant, Ruchir; Mohanan, Kishor (Synthesis, 2023)
Reported herein is an efficient α-arylation of α-fluoro-α-nitrosulfonylmethanes using diaryliodonium salts. A wide range of α-fluoronitrosulfonylmethane substrates underwent α-arylation smoothly to produce the corresponding adducts bearing a fully substituted fluorocarbon center in good to excellent yields. The protocol was subsequently shown viable for the α-arylation of α-cyano-α-fluorosulfonylmethane derivatives yielding highly valuable cyano building blocks.
Keywords: α-fluoro-α-nitrosulfonylmethanes; diaryliodonium salts; α-arylation; α-fluoro(phenylsulfonyl)acetonitriles; metal-free